Clays and Clay Minerals, Vol. 57, No. 5, 578–585, 2009. - Eick, Matthew J.; Luxton, Todd P.; Welsh, Holly A. (My University, 2009)
Numerous studies have investigated the ligand-promoted dissolution of Fe (oxyhydr)oxides. In natural environments, inorganic ligands can compete with organic ligands for surface sites on (oxyhydr)oxides which may influence dissolution rates. Published research of this interaction and its effect on the dissolution of (oxyhydr)oxides is rare. The objective of the present study was to examine the extent to which silica, as a naturally occurring competitive ligand added in the form of silicic acid, impacts the oxalate-promoted dissolution of the common soil Fe (oxyhydr)oxide goethite. Sorbed silica reduced the oxalate-promoted dissolution rate of goethite at all surface coverages investigated. As initial silica solution concentrations increased from 0.50 mM to 5.0 mM, relatively little change in the dissolution rate was observed. Fourier-transform infrared (FTIR) spectra indicated that, as silica-surface coverages increased, the silica underwent polymerization on the goethite surface. Initially, silicate was associated with surface functional groups, but as polymerization occurred some of the silica appeared to desorb from the goethite surface without being released into the bulk solution, suggesting that silica polymers formed discrete islands or surface clusters that grew away from the goethite surface rather than expanding epitaxially across the surface. Minimal changes were observed in the quantity of reactive goethite surface, which is responsible for the observed dissolution rates, as silica-surface coverages increased.
Progressive Formation Of Halloysite From The Hydrothermal Alteration Of Biotite And The Formation Mechanisms Of Anatase In Altered Volcanic Rocks From Limnos Island, Northeast Aegean Sea, Greece
gsccm57506-eic.pdf- 237KB
Keywords: Periodicals; Geology; Adsorption; Dissolution; Goethite; Oxalate; Polymerization; Silicic Acid